Paeoniflorin protects against intestinal ischemia/reperfusion by activating LKB1/AMPK and promoting autophagy. (August 2019) - Wen, Jin; Xu, Bin; Sun, Yuchao; Lian, Mengqiao; Li, Yanli; Lin, Yuan; Chen, Dapeng; Diao, Yunpeng; Almoiliqy, Marwan; Wang, Li
Graphical abstract: Abstract: Intestinal ischemia-reperfusion (I/R) injury is a common pathological process with high clinical morbidity and mortality. Paeoniflorin, a monoterpene glucoside, is found to have diverse health beneficial effects including autophagy modulation, anti-inflammatory, anti-apoptotic, and anti-oxidative effects. Based on our pre-experiments, we proposed that paeoniflorin could ameliorate intestinal I/R injury and restore autophagy through activating LKB1/AMPK signal pathway. Our proposal was verified using rat intestinal I/R model in vivo and intestinal epithelial cell line (IEC-6 cells) hypoxia/reoxygenation (H/R) model in vitro. Our results showed that paeoniflorin pretreatment exerted protective effects in rat intestinal I/R injury by reducing intestinal morphological damage, inflammation, oxidative stress, and apoptosis. Paeoniflorin restored H/R-impaired autophagy flux by up-regulating autophagy-related protein p62/SQSTM1 degradation, LC3II and beclin-1 expression, and autophagosomes synthesis without significantly affecting control IEC-6 cells. Paeoniflorin pretreatment significantly activated LKB1/AMPK signaling pathway by reversing the decreased LKB1 and AMPK phosphorylation without affecting total LKB1 both in vivo and in vitro . LKB1 knockdown reduced AMPK phosphorylation, suppressed LC3II and Beclin-1 level, and decreased the degradation of SQSTM/p62, and the knockdown weakened the effects of paeoniflorin in restoring the impaired autophagy flux in H/R injured IEC-6 cells, suggesting that paeoniflorin mitigated the intestinal I/R-impaired autophagy flux by activating LKB1/AMPK signaling pathway. Our study may provide valuable information for further studies.